The world community: methodological analysis of the concept - Ороховська, Л.А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article is methodological analysis of the concepts of "mankind," "humanity," "international community", "the international community" and others.